Molecular Epidemiological Characteristics of blaIMP-4-Carrying Klebsiella pneumoniae ST-11 in Hospitalized Patients - Xue YE; Zhang D; Du S; Chen D; Liu S; Peng T; Li C; Zhang J; Wang X (Infection and Drug Resistance)
Yu e Xue,1,* Dongmei Zhang,1,* Shuaixian Du,2,* Du Chen,3,* Shihan Liu,2 Tianfeng Peng,4 Chong Li,5 Jianchu Zhang,1 Xiaorong Wang1 1Department of Respiratory and Critical Care Medicine, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, Hubei, People’s Republic of China; 2Department of Clinical Laboratory, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, Hubei, People’s Republic of China; 3Department of Neurology, Guangzhou University of Chinese Medicine, Guangzhou, Guangdong, People’s Republic of China; 4Emergency Department, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, Hubei, People’s Republic of China; 5Gastrointestinal Surgery, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, Hubei, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaorong Wang; Jianchu Zhang, Department of Respiratory and Critical Care Medicine, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Number 1277, Jie Fang Rode, Wuhan, Hubei, 430022, People’s Republic of China, Tel + 86-27-85726707, Email rong-100@163.com; zsn0928@163.comPurpose: To investigate the molecular epidemiology and risk factors of carbapenem-resistant Klebsiella pneumoniae (CRKP) infection.Patients and Methods: Patient’s clinical data and CRKP strains were collected from November 2017 to December 2018 at a tertiary hospital in Wuhan, China. The antimicrobial susceptibilities, carbapenem-resistant genes, multi-locus sequence typing (MLST), homologous analysis, and risk factors for CRKP were determined.Results: A total of 203 CRKP strains were isolated, and 98.5% (200/203) of patients were nosocomially infected. The mortality rate was 17.7% (36/203). All 203 strains were confirmed as carbapenemases -producing strains. The most predominant carbapenemase gene was blaIMP-4 (81.3%, 165/203), followed by blaKPC-2 (25.1%, 51/203) and blaNDM-1 (23.2%, 47/205). Of the 203 strains, 28 (13.8%) had both blaKPC-2 and blaIMP-4 genes, 23 (11.3%) had both blaIMP-4 and blaNDM-1 genes, 20 (9.9%) had blaKPC-2, blaIMP-4 and blaNDM-1 three genes. MLST analysis showed that there were 48 ST typologies (including 7 new STs), of which ST-11 was the most prevalent (59.6%, 121/203). Phylogenetic analysis showed that 203 CRKP isolates came from 7 clusters and exhibited a strong correlation with the isolation source. eBURST analyses indicated that CRKP isolates have undergone different evolutionary processes. Patients with ST-11 CRKP underwent more mechanical ventilation (50% vs 32.9%, P=0.020) and gastric catheterization (15.7% vs 6.1%, P=0.042) within 3 months before sample collection, and also had higher drug-resistance rate than non-ST-11 CRKP. Comparing with CSKP (carbapenem-sensitive Klebsiella pneumoniae), gastrointestinal disease (odds ratio [OR]=6.168, P=0.003), nosocomial infection (OR=5.573, P=0.012), antibiotic exposure (OR=4.131, P=0.004), urinary catheterization (OR=3.960, P=0.031) and venous/arterial catheterization (OR=2.738, P=0.026) within the preceding 3 months were independent risk factors for CRKP infection.Conclusion: The IMP-4 was the most predominant carbapenemase and blaIMP-4 bearing Klebsiella pneumoniae ST-11 was spreading in the hospital. Nosocomial infections, antibiotic exposure, and urinary and venous/arterial catheterization within 3 months were the risk factors for developing CRKP infection.Keywords: Klebsiella pneumoniae, carbapenemase, multi-locus sequence typing, MLST, ST-11, IMP-4